8-13 Instalasi Lampu Tenaga Surya untuk Penerangan Jalan di Desa Cinta Rakyat, Kecamatan Samarang - sobirin, ruhiyat (Fakultas Teknik Universitas Islam Nusantara, 2020)
The condition of Cintarakyat Village is quite densely populated and still flows by rivers around the village area. People's professions vary from farmers, company employees, entrepreneurs, breeders, teachers, government employees, midwives etc. The other conditions in Cintarakyat Village are based on a survey that we conducted during PkM. The village has natural resources as well as community resources that are still beautiful and managed into various agricultural fields. It is known that people in rural areas are far from being developed. All activities are still simple. Most have not been touched by technological advances. The problem is the village of Cintarakyat whose roads are very dark with minimal lighting. Solar lamps were chosen because they are easy to install, durable and economical. Communities do not have to stretch cables from their homes or the PLN network to turn on the solar lights. In addition, to avoid theft of batteries for solar street lighting, as is the case with solar street lighting that has been previously installed in other areas, the PKM team chose to use solar lamps along with embedded batteries. The public street lighting installed by the PKM team also uses an automatic ignition system while the surroundings are not illuminated by light. The output is a solar powered lamp installed and used so that it can be used. The lamp is able to illuminate dark areas in very dark and minimally lit rice fields. Keywords: Solar lighting installation, Village